2011
DOI: 10.1021/ol102961x
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Cyclization, Dipolar Cycloaddition to Bridged Tricyclic Amines Related to the Daphniphyllum Alkaloids

Abstract: A tandem one-pot reaction of an aldehyde with a primary amine involving condensation and then cyclization (N-alkylation), followed by intramolecular dipolar cycloaddition of the resulting nitrone or azomethine ylide, provides a synthesis of bridged tricyclic amines. The reaction was most successful using hydroxylamine, and when the dipolarophile was an unsaturated ester, subsequent reduction of the N-O bond and cyclization to the lactam provided the core ring system of the yuzurimine, daphnilactone B, and buki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Coldham et al reported the first synthesis of the core ring system of the yuzurimine-type alkaloids by a cascade of condensation, cyclization, then intramolecular dipolar cycloaddition reactions [55]. In another study, a similar approach was successfully extended to bridged tricyclic compounds, yuzurimine B, daphnilactone B, and bukittinggine [56]. In 2009, two reports about asymmetric synthesis of cores common in daphnicyclidin-A-type alkaloids were published.…”
Section: Synthesis !mentioning
confidence: 99%
“…Coldham et al reported the first synthesis of the core ring system of the yuzurimine-type alkaloids by a cascade of condensation, cyclization, then intramolecular dipolar cycloaddition reactions [55]. In another study, a similar approach was successfully extended to bridged tricyclic compounds, yuzurimine B, daphnilactone B, and bukittinggine [56]. In 2009, two reports about asymmetric synthesis of cores common in daphnicyclidin-A-type alkaloids were published.…”
Section: Synthesis !mentioning
confidence: 99%
“…[9] Among the various available synthetic methodology, [3 + 2] cycloaddition play a key role for the construction of biologically significant five-membered heterocycles and azomethin ylide has been employed for the synthesis of pharmacologically important pyrrolidines, pyrrolizines and spiro compounds with high regio-and stereoselectivity. [10][11] Consequently, 1,2,3triazole derivatives show significant importance in the development of new perspective materials [12] and exhibit potential biological applications such as anti HIV-1, [13] antiparasitic, [14] antiplatelet, [15] antimicrobial against Gram positive bacteria, [16] selective b 3 adrenergic receptor agonism, [17] anticancer, [18] antimalarial [19] and anti-inflammatory activities. [20] 1,2,3-Triazole systems are remarkably stable towards hydrolytic, oxidative/ reductive conditions and enzymatic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our group has recently accomplished the asymmetric total syntheses of himalensine A 31 , dapholdhamine B 32 , and caldaphnidine O 33 . However, despite extensive synthetic studies [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] , total synthesis of yuzurimine-type alkaloids-the largest subfamily of the Daphniphyllum alkaloids-has not been achieved so far.…”
mentioning
confidence: 99%